Central African Economic and Monetary Community : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
The creation, in 1994, of the Central African Economic and Monetary Community (CEMAC) customs union was a major step in the regional integration process in central Africa. The implementation of the agreed regime by the member countries, however, has remained unsatisfactory. A 2002-03 initiative to improve policy implementation has largely stalled. Several recent initiatives concerning external trade provide new challenges and opportunities for welfare-enhancing reforms. Although the 1994 reforms that created the CEMAC customs union were a major step forward, the trade regime remains plagued by poor implementation.